Maximum power point tracking control for mechanical rectification wave energy converter - Jianan Xu; Yanpeng Zhao; Yong Zhan; Yansong Yang (IET Renewable Power Generation)
Abstract As a clean and renewable energy, wave energy has abundant reserves, and its reasonable development and utilization can effectively alleviate the problems of energy shortage and environmental pollution. This paper proposes a mechanical rectification wave energy converter. The reciprocating linear motion of the buoy is directly converted into the rotary motion through the ball screw. The magnetic coupling force transmission system is adopted to ensure the sealing of the device. Using mechanical rectification mechanism to ensure the service life of the generator. In addition, a dynamic model of the mechanical rectification wave energy converter is established. Through simulation analysis, the curve of power with load resistance is obtained. And there is an optimal load resistance value corresponding to the maximum power in different wave conditions. In order to improve the power generation efficiency, the maximum power point tracking control algorithm is designed based on the admittance differentiation method. By controlling the duty cycle of the switch tube in the Buck‐Boost chopper circuit, the variable load is realized, and then the maximum power point tracking control is realized. Finally, simulation analysis verifies the feasibility of the algorithm under different wave conditions.